1987
DOI: 10.1002/pen.760270511
|View full text |Cite
|
Sign up to set email alerts
|

Linear low density polyethylenes and their blends: Part 3. Extensional flow of LLDPE's

Abstract: The uniaxial extensional flow at 150°C of 11 linear low density polyethylenes (LLDPE) and one low density polyethylene was measured in a Rheometrics Extensional Rheometer. The presence of silicone oil did not affect the results. However, large effects of the molding time were observed. For specimens molded for 14 min, strain hardening was not observed for any gas‐phase polymerized LLDPE. As the molding time was increased to 40 min, the strain hardening was quite apparent, the elongational viscosity nearly doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…24,25 Schlund and Utracki pointed out the important phenomenon that the increased molding time induces a stronger strain-hardening property in LLDPE. 11 It was interpreted that the entanglement increases with time. The origin of the phenomenon is rooted in the fact that some of the PEs themselves are not homogeneous because of using no single phase catalyst or two-step polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Schlund and Utracki pointed out the important phenomenon that the increased molding time induces a stronger strain-hardening property in LLDPE. 11 It was interpreted that the entanglement increases with time. The origin of the phenomenon is rooted in the fact that some of the PEs themselves are not homogeneous because of using no single phase catalyst or two-step polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…A higher value of tensile stress at a given strain rate indicates higher melt strength. Previous research [4] has shown that the initial slope of the stress/strain curve for LLDPE resins correlates with the breadth of the resins' molecular weight distribution (MWD) and that LLDPE shows no strain hardening, even for HMW and broad MWD. Strain hardening is only seen in LDPE as a result of long chain branching.…”
Section: Rheologymentioning
confidence: 99%
“…It is very difficult to predict nonlinear melt viscoelasticity of miscible and immiscible blends from their linear viscoelasticity, because polymer behavior and phase structures are dramatically changed by large deformation. Nonlinear melt viscoelasticity has been most frequently investigated under uniaxial elongational deformation 7–20. Elongational rheology studies of polymer blends are classified into two groups.…”
Section: Introductionmentioning
confidence: 99%
“…Elongational rheology studies of polymer blends are classified into two groups. One is acrylonitrile–butadiene–styrene (ABS) polymers,7–12 and the other is polyethylene‐based blends 13–20…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation